Cognitive Flexibility and Coronavirus Anxiety: Mediating Role of Emotion Regulation and Maladaptive Schemas - Nooshin Boragh; Mokhtar Arefi; Saeedeh Alsadat Hosseini; Karim Afsharinia (Iranian Evolutionary Educational Psychology Journal, 2023)
Corona disease anxiety is one of the factors that threaten the mental health of working women, and it is very important to identify the psychological factors affecting it. This study aimed to investigate the structural relationship between Corona anxiety and cognitive flexibility and evaluate the mediating role of emotion regulation and early maladaptive schemas. The current research is a descriptive correlational study. Statistical population of this study was all the occupied women of Kermanshah city (Iran) in 2022, from which 364 people were selected by cluster random sampling method. The research tools include the Corona Disease Anxiety Scale (CDAS) (Alipour et al., 2018), the short form of the Young Schema Questionnaire (1998) (YSQ-SF), Cognitive Emotion Regulation Questionnaire (CERQ) (Garnefsky and Kraaij, 2006) and Cognitive Flexibility Inventory (Dennis & Vander Wal, 2010). The research data was analyzed using SPSS-25 software. Based on this, the path analysis method was used to analyze the research hypotheses. The evaluation of the proposed model had an acceptable fit. Path analysis identified the relationship between cognitive flexibility and corona anxiety, in addition, the findings indicated that cognitive flexibility is indirectly related to corona anxiety and predicts corona anxiety through the mediation of emotion regulation and early maladaptive schemas. In general, the findings showed that the implementation of interventions related to improving the psychological flexibility of working women by holding training classes and job webinars in the post-Corona era, in order to control and reduce anxiety, prepare and protect this group in possible relapses of infectious diseases is suitable.